Resource objective wildfires shifted forest structure and fuels toward pre-fire-exclusion conditions in a remote Arizona wilderness - Roccaforte, John P.; Huffman, David W.; Rodman, Kyle C.; Heinlein, Thomas A.; Crouse, Joseph E.; Fulé, Peter Z. (Fire ecology, 2025)
Background Large, severe fires are increasing throughout frequent-fire forests of the western United States due to warming climatic conditions, as well as legacies of early twentieth century land-use practices and anthropogenic fire exclusion. Resource objective (RO) wildfires—where naturally ignited wildfires are allowed to burn to accomplish management objectives—are increasingly accepted due to relatively low cost and flexibility on lands where mechanical treatments are not allowed (e.g., designated wilderness) or economically feasible. We previously implemented a field study across a portion of the Mount Trumbull Wilderness to identify differences between historical (ca. 1870) and contemporary (1999) forest structural conditions following 100 + years of fire exclusion. The study area subsequently experienced two RO wildfires (2012 and 2019), which presented an opportunity to (1) assess how closely post-wildfire (2023) conditions approximated historical forest conditions and (2) evaluate how RO fires influenced patterns of tree mortality and regeneration. Results Reconstructed forest structure was made up of open stand conditions (density: 62 trees ha −1 ; basal area: 9 m 2 ha −1 ) with large ponderosa pines (quadratic mean diameter: 42 cm). By 1999, the site was dominated by closed-canopy stands with many small-diameter trees. In 2023, following the two RO wildfires, tree density, basal area, and canopy cover were significantly reduced (20–50%), and tree size significantly increased. Ponderosa pine regeneration density declined relative to pre-fire levels, whereas regeneration of sprouting hardwood species increased. About half of the old trees (i.e., pre-dating ca. 1870) that were alive in 1999 died by the end of the study period, likely due to effects of fire-caused injury and drought. High-severity patch sizes in each fire were relatively small (6.2–46.6 ha) and within the historical range of variability for southwestern ponderosa pine ecosystems. The 2012 fire reduced remotely sensed fire severity in 2019. Conclusions Overall, RO fires shifted forest structure in a remote wilderness area toward open conditions that were historically present at the site, and likely reduced vulnerability to severe fire in the future. However, tree density remained six times higher than historical levels, and managers should consider allowing future RO wildfires to burn within the wilderness to further reduce tree density and accomplish ecological restoration goals.